Delinquent Youth Concentration and Juvenile Recidivism. Issue 7 (3rd July 2021) - Powell, Zachary A.; Craig, Jessica M.; Piquero, Alex R.; Baglivio, Michael T.; Epps, Nathan
ABSTRACT: Examining the environmental correlates of deviant behavior is a large area of interest that continues to promote much research in criminology. Recent attention has been given to understanding the effects of an elevated concentration of offenders on an individual's likelihood of recidivism. To our knowledge, no study has explored whether an elevated delinquent youth concentration negatively affects the recidivism of a juvenile population. Using data from a large number of adjudicated delinquents on community supervision from the state of Florida, mixed effects logistic regression analyses indicate that increases in delinquent youth concentration contribute to an increased risk of reoffending for younger, but not older, juvenile offenders. Future research directions and policy implications are also discussed.